Bad jobs and low inflation - Renato Faccini; Leonardo Melosi (Danmarks Nationalbank, 2020)
The low rate of inflation observed in the U.S. over the entire past decade is hard to reconcile with traditional measures of labor market slack. We show that an alternative notion of slack that encompasses workers' propensity to search on the job explains this missing inflation. We derive this novel concept of slack from a model in which a drop in the on-the-job search rate lowers the intensity of interfirm wage competition to retain or hire workers. The on-the-job search rate can be measured directly from aggregate labor-market flows and is countercyclical. Its recent drop is corroborated by micro data.
Keywords: E31; E37; C32; 330; Missing inflation; on-the-job search; employment-to-employment rate; labor market slack; Phillips curve; cyclical misallocation